Nature Of Information Provided And Quality Of Sustainability Reports Assurance Statements Of Fortune Global 500 Companies - Achmad, Tarmizi; Faisal, Faisal; Ulum, Muhammad Bahrul (Journal of Applied Business Research, 2017)
The objective of this study is to investigate how the quality of assurance statement varies among the different assurance providers (accounting versus non-accounting firms). The sample consists of one hundred thirty-five of Fortune Global 500 companies for the year 2014. Independent sample t-test is used to determine how the quality of assurance statement differs among various assurance providers. The result shows that accounting firms still dominate the sustainability report assurance market (75.56 per cent), while non-accounting firms is 24.44 per cent. However, in terms of quality score of assurance statement, non-accounting assurance providers (consultant) value higher than accounting firms for all aspects of report content (reporting format, assurance procedures and recommendations and opinion). The implication of this finding suggests that the company not only to consider the reputation of the assurance provider, but the more important thing is competence and expertise in the field of sustainability reporting. Despite the growing interest research in assurance, this study is one of the few studies that measure assurance quality by content analysis.